A survey on relationship between intellectual capital and organizational innovation: A case study of banking industry - Gholam Panahandeh; Ahmad Ahmadkhani (Management Science Letters)
This paper presents an empirical investigation to study the relationship between intellectual capital and organizational innovation in an Iranian bank named Ghavamin located in city of Zanjan, Iran. The proposed study uses a questionnaire introduced by Bontis [Bontis, N. (1999). Managing organisational knowledge by diagnosing intellectual capital: framing and advancing the state of the field. International Journal of technology management, 18(5), 433-462.] for measuring the effect of intellectual capital and designs a questionnaire to measure organizational innovation. The questionnaires are distributed among 40 randomly selected managers and regular employees and using Pearson correlation as well as stepwise regression model, the study has detected positive and meaningful relationship between intellectual capital and organizational innovation.